On the acceptability of multiple interrogatives in Italian - Neagu, Anda (Working papers in Applied Linguistics and Linguistics at York, 2021)
Multiple interrogatives exhibit cross-linguistic variation from a typological point of view. Standard Italian, in particular, is considered to be a language disallowing these constructions, an analysis based on the interaction between whPs and focused constituents in this language. I argue that previous analyses of multiple wh-questions in Italian need to be integrated with novel data, and that these structures are at least marginally acceptable. Specifically, I illustrate data from a preliminary experiment involving acceptability judgements on a 5-point Likert scale that tested whether native Italian speakers consider multiple interrogatives acceptable. While this is still a preliminary investigation, the results indicate that younger native Italian speakers tend to accept these constructions. I suggest that the presence of two whPs within the same clause in Italian can be analyzed as a language contact phenomenon, with English being the source language, in line with the sociolinguistic literature on this topic.